Economics of South African townships, special focus on Diepsloot - Mahajan, Sandeep (World Bank Group, 2014)
Countries everywhere are divided within into two distinct spatial realms: one urban, one rural. Classic models of development predict faster growth in the urban sector, causing rapid migration from rural areas to cities, lifting average incomes in both places. The situation in South Africa throws up an unconventional challenge. The country has symptoms of a spatial realm that is not not rural, not fully urban, lying somewhat in limbo. This is the realm of the country's townships and informal settlements (T & IS). In many ways, the townships and especially the informal settlements are similar to.